Odpowiedzi

  • Roma
  • Community Manager
2010-01-25T15:47:08+01:00
A) 1 + sinα + cosα + tgα = 1 + sinα + cosα + sinα/cosα = cosα/cosα + sinα*cosα/cosα + cosα*cosα/cosα + sinα/cosα = 1/cosα * (cosα + sinα*cosα + cosα*cosα + sinα) = 1/cosα * (cosα + cosα*cosα + sinα*cosα + sinα) = 1/cosα * [cosα*(1 + cosα) + sinα*(cosα + 1)] = 1/cosα *(cosα + sinα)*(1 + cosα)

b) cosα + sin2α - cos3α = cosα + 2*sinα*cosα - 4*cos³α + 3*cosα = 2*sinα*cosα - 4*cos²α + 4*cosα = 2cosα * (sinα - 2*cos²α + 2) = 2cosα * [sinα - 2*(1 - sin²α) + 2] = 2cosα * (sinα - 2 + 2*sin²α + 2) = 2cosα * (sinα + 2*sin²α) = 2cosα * [sinα*(1 + 2*sinα)] = 2cosα *sinα*(1 + 2*sinα)
5 3 5